THE CAUSAL FACTORS OF OFFICIAL MISCONDUCT COMMITTED BY ABUSE OF OFFICE AND THE MAIN CIRCUMSTANCES TO DETERMINE IN THE INVESTIGATION (Law and world, 2019)
The Author of the article identiﬁes the causal factors of ofﬁcial misconduct committed by abuse of ofﬁce and classiﬁes it into ten categories. According to the author, for the effective investigation of criminal cases concerning the ofﬁcial misconduct, ﬁrst of all, it is vital to accurately prepare strategies and tactics of an investigative plan, outline the factual circumstances, which later will become the subject of proof. Based on the analyzes regarding speciﬁcs of ofﬁcial misconduct, the author offers ﬁve conditional criteria. These criteria must be determined and examined in each investigation process of ofﬁcial misconduct, promoting to resolve criminal cases, as well as, to obtain and preserve the evidence in accordance with the established procedures.